PENERAPAN STRATEGI QUIZ TEAM DALAM MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII-7 SMP NEGERI 21 PEKANBARU - Lauda, Niki Lauda S; ', Armis; Hutap, Nahor Murani Hutapea Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is based on the low of students math achievement at grade VII-7 Junior High School 21 Pekanbaru in even semester the academic years 2013/2014. It can be seen from achievement of Mastery Minimum Criteria for set lesson, only 12 students (30%) by learning process conducted teacher-centered (conventional). The research was classroom action research to improve learning process and improve students math achievement by implementing Quiz Team strategy in cooperative learning. The research subject as much as 40 students, consist of 20 male and 20 female. The research consist of two cycles and at the end of every cycle carried out math test. The instruments of data collecting are observation sheets and math achievement tests. The data of observation were analyzed in narrative descriptive and the data of math achievement were analyzed in descriptive statistical. The result of narrative descriptive analysis showed that there is the improvement of learning process after the action on the first and second cycles. The result of research showed that there is an increase percentage amount students from base core to math test I, that is 30% until 50% as much as 20% and from math test I to math test II, that is 50% until 80% as much as 30%. The conclution: the implementation Quiz Team strategi in cooperative learning could improve learning process and improve student’s math achievements at grade VII-7 Junior High School 21 Pekanbaru in even semester the academic years 2013/2014. Key Words: Students Math Achievement, Quiz Team Strategi, Cooperative Learning,Classroom Action Research